THEORETICAL AND LEGAL-NORMAL BASIS OF VALIDATION OF NON-RESIDENTIAL REAL ESTATE - Hajiboyeva Kamola Baxtiyor qizi (Western European Studies, 2025)
This article examines the theoretical and regulatory foundations for the valuation of real estate properties, with a particular focus on non-residential premises. It analyzes ways to improve the methods used in their valuation. It analyzes the importance of modern valuation methodologies, the development of market mechanisms, and the need to accurately determine the value of property. It also examines the methods used in the valuation process, their advantages and disadvantages, and provides practical suggestions for implementing advanced international practices
Keywords: Commercial real estate; non-residential properties; valuation methodology